Water Pressure Switch Design Using 555 Timer - Abdalla Milad Faraj; Musbah Al-Mahdi Al-Jadi; Ahmed Saed Ishleebtah (African Journal of Advanced Pure and Applied Sciences, 2025)
For industrial processes to be done properly, a system has to work under specific pressures. Safety considerations as well demand monitoring and “measuring” operation pressures and taking control over them to therefore ensure the equipments and lines in the systems don’t exceed the permissible pressure as well as to ensure they are not destroyed or damaged in case the pressure is increased over a certain limit. These objectives can be attained by using sensors and pressure switches which are considered from the most important components in the industrial processes, specifically in the hydraulic and aerial systems. This project is set for designing and constructing an automatic pressure switch for a pressure source (pump), to automatically control water pressure which happens as a result of its influx in the hydraulic systems. Taking control over this process is done by using (SR flip flop) which receives a controlling signal from the (limit switch). The latter could sense the movement of the used pressure sensor. After that, a model is applied for a domestic water pump to control its operation. The model could protect the pressure when it increases over a certain limit, the flip-flop stops operating the source of the pressure (the pressure). At that, the model has been put into test and the results were very good as expected.